Ring the BELL and tie the KNOX: roles for TALEs in gynoecium development - Arnaud, Nicolas; Pautot, Véronique (Frontiers in Plant Science, 2014)
Carpels are leaf-like structures that bear ovules, and thus play a crucial role in the plant life cycle. In angiosperms, carpels are the last organs produced by the floral meristem and they differentiate a specialized meristematic tissue from which ovules develop. Members of the three-amino-acid-loop-extension (TALE) class of homeoproteins constitute major regulators of meristematic activity. This family contains KNOTTED-like (KNOX) and BEL1-like (BLH or BELL) homeodomain proteins, which function as heterodimers. KNOX proteins can have different BELL partners, leading to multiple combinations with distinct activities, and thus regulate many aspects of plant morphogenesis, including gynoecium development. TALE proteins act primarily through direct regulation of hormonal pathways and key transcriptional regulators. This review focuses on the contribution of TALE proteins to gynoecium development and connects TALE transcription factors to carpel gene regulatory networks.